The relationship between vitamin D receptor gene and TREM‐1 gene polymorphisms and the susceptibility and prognosis of neonatal sepsis. Issue 5 (31st March 2022) - Xiao, Li; Que, Shengshun; Mu, Lei; Zheng, Rongxiu
Abstract: Objective: The objective of this was to study the relationship between vitamin D receptor (VDR) and triggering receptor expressed on myeloid cells 1 (TREM‐1) gene single‐nucleotide polymorphisms (SNP) and neonatal sepsis susceptibility and prognosis. Methods: The blood of 150 neonatal sepsis patients and 150 normal neonates was collected, and genomic DNA was extracted. Sanger sequencing was used to analyze the genotypes of VDR rs739837 and TREM‐1 rs2234246. Results: Vitamin D receptor rs739837 locus GT, TT genotype, dominant model, and recessive model were all protective factors for sepsis (0 < OR < 1, p < 0.05). The risk of sepsis in carriers of the rs739837 G allele was 0.65 times that of the rs739837 T allele (95% CI: 0.50–0.83, p < 0.001), CT, TT, dominant model, and recessive model at rs2234246 were risk factors for sepsis (OR > 1, p < 0.05). The risk of sepsis in carriers of the rs739837 T allele was 1.38 times that of carriers of the C allele (95% CI: 1.16–1.61, p < 0.001). The polymorphisms of VDR gene rs739837 and TREM‐1 gene rs2234246 were not significantly correlated with the survival of patients with neonatal sepsis ( p > 0.05). Conclusion: Vitamin D receptor gene rs739837 locus G>T is associated with a reduction in the risk of neonatal sepsis, TREM‐1 rs2234246 C>T is associated with the increased risk of neonatal sepsis, but none of them was significantly associated with the prognosis of neonatal sepsis. Abstract : A total of 150 neonatal sepsis patients and 150 normal neonates' VDR rs739837 and TREM‐1 rs2234246 SNPs were analyzed. Multivariate logistic regression was used to analyze the relationship between VDR rs739837 and TREM‐1 rs2234246 SNPs and the susceptibility and prognosis of neonatal sepsis.